2012
DOI: 10.1007/s00723-012-0335-8
|View full text |Cite
|
Sign up to set email alerts
|

Fast Dissolution Dynamic Nuclear Polarization NMR of 13C-Enriched 89Y-DOTA Complex: Experimental and Theoretical Considerations

Abstract: The yttrium complex of 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetra(1 0 -13 C-acetic acid) [ 13 C]DOTA was synthesized. Fast dissolution dynamic nuclear polarization (DNP) nuclear magnetic resonance (NMR) studies revealed that the 89 Y, 13 C, and 15 N nuclei present in the complex could be co-polarized at the same optimum microwave irradiation frequency. The liquid-state spin-lattice relaxation time T 1 of these nuclei were found to be reasonably long to preserve some or most of the DNP-enhanced polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…However, we note that it is also possible that the physics of DNP at 6.5 K or higher may be quite different for DNP done at T ~1K. As mentioned before, mounting experimental evidence 6,7,41,42 suggest the thermal mixing is the predominant DNP mechanism for low-γ nuclei such as 13 C, 89 Y, etc., at least at DNP conditions of 3.35 T and T ~1 K in which we have performed the experiments. Further combined DNP and ESR studies at these conditions may be needed to fully clarify these effects.…”
Section: Resultsmentioning
confidence: 64%
“…However, we note that it is also possible that the physics of DNP at 6.5 K or higher may be quite different for DNP done at T ~1K. As mentioned before, mounting experimental evidence 6,7,41,42 suggest the thermal mixing is the predominant DNP mechanism for low-γ nuclei such as 13 C, 89 Y, etc., at least at DNP conditions of 3.35 T and T ~1 K in which we have performed the experiments. Further combined DNP and ESR studies at these conditions may be needed to fully clarify these effects.…”
Section: Resultsmentioning
confidence: 64%
“…17,18,20,21,31,34,49 Trityl OX063, the stable organic radical used in this work, has a very narrow EPR linewidth that makes it ideal for polarizing low-γ nuclei such as 13 C. When using this free radical to polarize low-γ nuclei such as 13 C spins, DNP data at 3.35 T and temperatures close to 1 K have shown indications of thermal mixing (TM) as the predominant DNP mechanism. 24,[50][51][52][53] Other DNP data at similar conditions suggested that the mechanism could be a combination of the solid effect (SE) and cross effect (CE). [54][55][56] Unlike the solid effect (SE) 57 and the cross effect (CE), 54,58 TM is a many-spin model for polarization that treats spin interactions as thermodynamic reservoirs.…”
Section: Resultsmentioning
confidence: 94%
“…In the solid effect regime where the ESR linewidth D is much smaller than the nuclear Larmor frequency ν n these optimum polarization peaks are expected to appear at ν e ± ν n [4, 5]. However, considering the ESR linewidths of these free radicals are wider than or comparable to the 13 C ν n , the expected predominant DNP mechanism for 13 C samples here is the thermal mixing process [28, 29]. The shape of the microwave DNP spectra in this regime can be approximated by the Borghini model, which predicts the nuclear spin temperature as a function of the ESR line shape [30].…”
Section: Discussionmentioning
confidence: 99%